Structure and efflux mechanism of the yeast pleiotropic drug resistance transporter Pdr5 - Andrzej Harris; Manuel Wagner; Dijun Du; Stefanie Raschka; Lea-Marie Nentwig; Holger Gohlke; Sander H. J. Smits; Ben F. Luisi; Lutz Schmitt (Nature Communications, 2021)
Pdr5 is an ABC transporter conferring multidrug resistance to pathogenic fungi. Here, structural analysis of Pdr5 provides insights into the transport mechanism featuring asymmetric movements of Pdr5 domain and enabling efflux of a broad spectrum of compounds.